Nawab Faizunnesa's Rupjalal - Caudhurāṇī, Phaẏajunnesā, 1834-1903 (Women and gender, the Middle East and the Islamic world, 2009)
"Nawab Faizunnesa (1834-1903) challenged established notions regarding women's position in a Muslim society in colonial Bengal. Her RupJalal was the first literary text written by a Bengali Muslim woman. The translated text is placed in the historical context of colonialism and the nationalist movement of colonial Bengal. An analysis of the text is also included in order to invite readers to explore the woman question in context of Islam and/in imperial society. With the translated text, along with a critical overview and textual analysis, this book traces in Faizunnesa's life and works the emergence of a self-conscious female voice by addressing the issues of social, political, and economic marginality of women in an Islamic, nationalist, and imperialist culture of colonial Bengal."--Jacket